2016
DOI: 10.4103/1119-3077.164336
|View full text |Cite
|
Sign up to set email alerts
|

Using cone beam computed tomography to examine the prevalence of condylar bony changes in a Turkish subpopulation

Abstract: The prevalence of degenerative condylar bone changes increased with increasing age and was more frequent in women and right condyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…could be because their sample consisted of orthodontic patients who are usually young, as studies have shown that the severity of TMJ osseous changes increases with increasing age 20, 21. One reason for the relatively higher rate of TMJ degenerative changes in our study could be that the sample was female, and several studies have shown that the TMJ degenerative changes are higher among women 20, 22…”
Section: Discussionmentioning
confidence: 83%
“…could be because their sample consisted of orthodontic patients who are usually young, as studies have shown that the severity of TMJ osseous changes increases with increasing age 20, 21. One reason for the relatively higher rate of TMJ degenerative changes in our study could be that the sample was female, and several studies have shown that the TMJ degenerative changes are higher among women 20, 22…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the above nine morphologic parameters were used to investigate the TMJ morphology in this study. The 2D CBCT measuring method has been validated in the related studies [18, 19, 2224]. The 3D measuring method also has been used to evaluate the condylar morphology [15, 17, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The degenerative changes of the condyles were classified according to previously reported definitions as follows: 16 flattening (Figure 2a); sclerosis (Figure 2b); erosion (Figure 2c); osteophytes (Figure 2d); and combination of two or more degenerative condylar changes (Figure 2e).…”
Section: Diagnostic Classification For Condylar Bone Changementioning
confidence: 99%